Pengaruh Model Pembelajaran Think Pair Share terhadap Keaktifan Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas XI SMA Swasta HKBP Doloksanggul Tahun Pembelajaran 2024/2025 - Benita Ariany Nainggolan; Senida Harefa; Ordekoria Saragih; Rusmauli Simbolon; Tahadodo Waruwu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study was to determine the effect of the Think Pair Share learning model on the learning activity of Christian Religious Education and Character Education of class XI students of HKBP Doloksanggul Private High School in the 2024/2025 Academic Year. The research hypothesis is that there is an effect of the Think Pair Share learning model on the learning activity of Christian Religious Education and Character Education of class XI students of HKBP Doloksanggul Private High School in the 2024/2025 Academic Year. This research method is the Quasi Experimental Design method using the Nonequivalent Control Group Design. The population of all class XI students of HKBP Doloksanggul Private High School in the 2024/2025 Academic Year who are Protestant Christians is 159 students and is divided into 5 classes. The research sample was determined using a purposive sampling technique, namely 30 students in class XI-4 as an experimental class using the Think Pair Share learning model and 33 students in class XI-2 as a control class using the usual treatment (conventional class). The research instrument was a closed questionnaire consisting of 30 items. The research questionnaire data was analyzed using the average difference test formula (N-Gain Score). The average pretest and posttest scores at the first and second meetings of the experiment were 3.06 and 3.77, and for the first and second meetings of the pretest and posttest in the control class were 2.75 and 3.00. So the overall average score of the experimental class is 0.7570 in the high category. The overall average score for the control class is 0.1930 in the low category. Then the t-test obtained a value of t count = 14.170> t table (α = 0.05; df = 61) = 2.000, so H0 is rejected and Ha is accepted. The study concluded that there is an influence of the Think Pair Share learning model on the activeness of learning Christian Religious Education and Character Education of class XI students of HKBP Doloksanggul Private High School in the 2024/2025 Academic Year.